Development of Multidisiplinary-Based Islamic Education Teaching Materials to Support Contextual Learning: A Theoretical Review - Nadia Apriliani Gani; Kasim Yahiji; Mujahid Damopilii (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Islamic Religious Education (IRE) plays an important role in shaping students’ character, spirituality, and moral values. However, many IRE teaching materials remain conventional, text-based, and insufficiently connected to students’ real-life contexts. This article aims to analyze the concept of IRE teaching materials, multidisciplinary approaches in education, principles of multidisciplinary-based teaching material development, and development models used in IRE learning. This study employed a literature review method by examining approximately 15 relevant scientific sources, including journal articles, books, and previous research studies published between 2020–2026. The review findings reveal three major themes: (1) the need for integrating Islamic values with science, social studies, and humanities; (2) the importance of contextual and student-centered teaching materials; and (3) the use of systematic development models such as ADDIE and Research and Development (R&D). The synthesis of the literature indicates that multidisciplinary-based IRE teaching materials contribute to creating more contextual, meaningful, innovative, and 21st-century-oriented learning. In addition, this approach supports the development of critical, creative, collaborative, and communicative thinking skills while strengthening the integration of religious and scientific knowledge. Therefore, the development of multidisciplinary-based IRE teaching materials is considered an essential strategy for improving the quality and relevance of Islamic education in contemporary learning contexts.